STAND SIMULATED PROCESS FOR TESTING PUMPS - M. D. Gammer; S. P. Kolesnikov; G. V. Kolesov (Литьë и металлургия)
The article deals with the creation of simulation models for modern learning tools – simulators based on soft- ware and hardware platform as in the training of specialists in production, as well as in teaching students at the university.